Periodontal diseases in Down syndrome during childhood: a scoping review - Valentin Vergier; Anne-Margaux Collignon; Marjolaine Gosset; Anne-Laure Bonnet (BMC Oral Health)
Abstract Background Down syndrome (DS) is a genetic condition that involves the deregulation of immune function and is characterized by a proinflammatory phenotype leading to an impaired response to infections. Periodontitis is a highly prevalent chronic inflammatory disease. It has been shown that adults and teenagers with DS are more susceptible to this disease, but a similar correlation in DS children remains elusive. This systematic scoping review aims to address this knowledge gap by examining periodontitis in DS children, with a secondary objective of elucidating the underlying mechanisms involved. Methods Our primary search was conducted via the PubMed/MEDLINE database and Google Scholar, covering the period from 1951–July 1st, 2024. Primary studies written in English or French were included. The excluded articles were reviews, in vitro or animal studies, studies on teenagers or adults, and studies involving patients with disabilities other than DS. The quality of evidence was assessed via the Newcastle‒Ottawa scale for observational studies and a published tool for evaluating the quality of case reports and case series. Results The initial electronic database search yielded a total of 2431 articles. 58 full-text articles, comprising seven cross-sectional studies, 36 case‒control studies, seven cohort studies, and eight case reports and case series, were included in the review. Compared with healthy children or children with disabilities, DS children appear to have more severe periodontal inflammation. However, the evidence is inconclusive regarding the presence of bone loss, with studies divided on this issue. Local risk and etiopathogenetic factors do not seem to play a significant role in increased inflammation. Instead, this difference could be attributed to the general proinflammatory phenotype of children with DS. Conclusions DS children seem to have higher periodontal inflammation than other children, but no periodontal bone loss. Investigating periodontal inflammation in DS children could provide valuable insights into the deregulation of immune function in these patients.